Model Pembelajaran Multi Intelegensia dan Multi Talenta Imam Ali Asy Syaukani - Siti Qomariyah; Wendy Asswan Cahyadi (LP. Ma'arif Janggan Magetan, 2022)
The number of teachers who do not understand the theories, models and methods of learning, is often a problem to achieve goals in Islamic education. This study uses a descriptive qualitative approach to analysis through library research which examines concepts and content (content analysis) related to theories and learning models in Islamic Education in Muhammad ibn Ali asy Syaukani's book, Adabu Talib wa Muntahal Arib. The data analysis procedures are: data collection, data reduction (data reduction/sorting), data display (data presentation), and conclusion drawing/verification (drawing conclusions/verification). To test the validity of the data, the researchers used test equipment: reference materials, confirmability, triangulation and transferability. The results of this study are the importance of the revival of knowledge and the tradition of science, the requirements for having multiple intelligences and abilities, and a brilliant learning model, namely the first multiple intelligences and multiple talents model, the mastery model of various disciplines. second, the concept of intelligence and dual abilities, namely learning, teaching and working.